Built on the Ruins of Empire : British Military Assistance and African Independence - Whitaker, Blake (Book collections on Project MUSE., 2022)
"During the Cold War the British government oversaw the transition to independence of dozens of colonies. Often the most challenging aspect of this transition was the creation of a national army from colonial forces. In Built on the Ruins of Empire, Blake Whitaker examines this process in Kenya and Zambia and how it set the course for the creation of the army in Zimbabwe and looks at three themes as they intersect in African military history: British decolonization, race relations, and the Cold War. While transition was a difficult process in places such as Ghana and Nigeria, it was compounded by the racial tensions in Kenya, Zambia, and Zimbabwe. All three were settler colonies, and home to a sizeable community of white Europeans who controlled the levers of power and economic prosperity. This book focuses on the difficulties that arose in creating a cohesive and apolitical military force in these racially charged Cold War environments, and demonstrates that the challenges faced by the British training missions in Kenya and Zambia taught London important lessons about the emerging postcolonial world"--